Analysis of the Concepts and Principles of Educational Philosophy from Western, Eastern, and Islamic Perspectives and Their Contribution to the World of Education - Leny Nurdiyaningsih; Iskandar; Juliana; Noevandi (Journal Informatic, Education and Management (JIEM), 2026)
This article outlines an analysis of the concepts and principles of educational philosophy using a literature analysis approach, including articles, journals, and books, to identify its contribution to the world of education. Educational philosophy is a branch of philosophy that plays a crucial role in formulating the direction, goals, and methods of education. Through a literature study of the thoughts of Western, Eastern, and Islamic philosophers, we analyze the differences and similarities in their views on education. Western educational philosophy concepts emphasize rationality, individuality, and freedom of thought. Eastern educational philosophy concepts emphasize balance, morality, and harmony. Islamic educational philosophy, on the other hand, is based on revelation, the integration of knowledge and morality, and the ultimate goal of salvation and happiness in this world and the hereafter. Therefore, the principles of educational philosophy developed by these three approaches are relevant to the development of today's more contextual and holistic education. The analysis shows that educational philosophy not only plays a significant role in the formal teaching process but also forms fundamental aspects of character formation and the instilling of individual and societal values.